Vascular Functions and Brain Integrity in Midlife: Effects of Obesity and Metabolic Syndrome. (23rd June 2014) - Haley, Andreana P.
Abstract : Intact cognitive function is the best predictor of quality of life and functional ability in older age. Thus, preventing cognitive decline is central to any effort to guarantee successful aging for our growing population of elderly. The purpose of the work discussed in this outlook paper is to bridge knowledge from basic and clinical neuroscience with the aim of improving how we understand, predict, and treat age- and disease-related cognitive impairment. Over the past six years, our research team has focused on intermediate neuroimaging phenotypes of brain vulnerability in midlife and isolating the underlying physiological mechanisms. The ultimate goal of this work was to pave the road for the development of early interventions to enhance cognitive function and preserve brain integrity throughout the lifespan.